Penerapan Hazard Analysis Critical Control Point (HACCP) Pada Produksi Bontot: Pangan Lokal Banten - Nia Ariani Putri; Zulfatun Najah; Winda Nurtiana; Dian Anggraeni (Jurnal Teknologi dan Industri Pertanian Indonesia, 2022)
Geographically, the province of Banten is surrounded by the ocean so that the area is rich in processed fish products such as milkfish satay, shredded milkfish, and bontot. Bontot is a Banten’s local food made from payus fish which is considered to be lacking in development. This can be seen mainly in terms of the production process which is still very simple and does not apply good manufacturing practices (GMP). The purpose of this research is to help producer to understand and apply GMP so that the quality of bontot products can be better. The research method used is by conducting a survey using the intensive interview method. The results show that some producers have not implemented GMP in their production process, so that the preparation of the HACCP draft is considered important to assist producers in the production process. Of the several raw materials and production processes that constitute CCP are fish, the process of receiving raw materials, packaging, and storage. Preventive and corrective actions are needed to minimize these hazards. Thus, the mentoring process needs to be carried out in implementing the HACCP that has been prepared to ensure the quality and food safety of the bontot product.